SEORANG PENDERITA INFARK MIOKARD AKUT TANPA ELEVASI SEGMEN ST DENGAN SINDROMA QT MEMANJANG - Ketut Angga Aditya Putra Pramana; Yusra Pintaningrum; Jatno Karjono (Faculty of Medicine Universitas Mataram, 2022)
We reported a 64-year-old woman was admitted to Emergency Department of dr.Soetomo hospital with fainting and previous chest discomfort, then we diagnosed this patient with Non ST Elevation Myocard Infarct, diabetes mellitus, hypertension stage II, and long QT syndrome (LQTS) with torsades de pointes episodes. There are two important tests to determine LQTS, electrocardiogram (ECG) and a genetic test. Two kinds of LQTS, congenital LQTS is caused by mutations in genes coding, and acquired LQTS often is associated with drugs or metabolit abnormalities. Myocardial ischemia could change QT interval regionally in the area of ischemia, and these changes are related to extent and severity of coronary atherosclerosis. There are two major treatment options for patients with LQTS, medications and ICD/pacemaker implantation. Beta-blockers are the drugs of choice.